Annotated list of ichthyofauna of inland and coastal waters of Sakhalin Island. 3. Families Priacanthidae-Sebastidae - Dyldin, Yury V.; Orlov, Alexei M. (Journal of Ichthyology, 2021)
The third part of the report represents the annotated list of fish species found in the marine (within a 200-mile zone), brackish, and fresh waters of Sakhalin: 145 species from 2 orders, 22 families, and 61genera.